PERENCANAAN TIMBUNAN PADA AREA PERLUASAN APRON DENGAN MEMPERHITUNGKAN ADANYA PENURUNAN TANAH DI BANDAR UDARA SILAMPARI LUBUKLINGGAU - Khofivah Diyah Permatasari (Approach : Jurnal Teknologi Penerbangan, 2021)
Silampari Airport is one of the airports that is managed by The Ministry of Transportation, which is located 10 kms west of Lubuklinggau City, South Sumatera. Silampari Airport owns an apron with the dimension of 130 m x 100 m with a flexible pavement that has a PCN of 49 F/C/X/T. In accordance with the masterplan, a widening of the apron to become 278 m x 100 m will be carried out. Meanwhile, the condition of the widening area is a swamp with an elevation difference from the existing apron approximately 9 meter from the subgrade. The purpose of this research is to find out how much embankment is needed and how much of soil is degraded caused by the consolidation. The staged construction method used in this research is a method of filling shallow soil with the aim of accelerating the process of soil consolidation. Based on the result of the planning that has been done, the required embankment height will be 11,461 meters by calculating both the embankment and the working load. Embankment needs to be carried out with a staged construction method, it needs to be done within 2 stages with a consolidation size of 0,331 meters from the results of manual calculations and 0,147 from the analysis using PLAXIS software. Then the waiting period for consolidation is 2,488 years according to the results of manual calculations and 2,263 years from the analysis using PLAXIS 8.2 software. The results of the analysis, it was found that consolidation and waiting time have an insignificant differences in values. This means that the modeling has been done correctly, the difference of the numbers on the waiting time for consolidation was caused by the differences in the parameters used in PLAXIS, namely the permeability coefficient, while in the manual calculation the Cv value is used